THE SUBSTANTIATION OF ARCHITECTURAL-PLANNING TRANSFORMATIONS OF URBAN PUBLIC SPACES WITH THE ACCOUNT OF THE PRINCIPLES OF BIOPOSITIVITY - Sidorova, Viktoriia; Zhivitsa, Viktoriia; Mosyakin, Dmitry (Journal of Applied Engineering Science, 2019)
This article presents the results of a scientific study conducted within the framework of an intra-university grant. The work was partially supported by the V.I. Vernadsky Crimean Federal University Development Program for 2015-2024. The analysis of the world experience in the design of biopositive public spaces in various cities of the world is considered, the methods for the formation of a sustainable biopositive urban space are outlined in the theoretical works of leading specialists in various directions. Spaces of Crimean cities, in particular its capital - Simferopol, listed a number of problems of the following public urban spaces : areas, landscape objects, pedestrian streets, embankment, etc., formed as a result of the development and growth of the modern city, the results of surveys conducted by the authors (questionnaires, social questions) among guests and local population of Crimean cities. wishes of the residents of Simferopol city, Alushta city and Chernomorskoye settlement to architectural-planning, composition-landscape and artistic expressive qualities of urban public spaces. A short characteristic of the most popular urban spaces is given, their advantages and disadvantages are indicated. The requirements of residents and guests of these the Crimean cities to the qualitative and quantitative characteristics of the material and technical and vegetable content of the urban environment are analyzed. Practical recommendations on the architectural and planning reconstruction of transport and pedestrian units, squares, garden and park facilities, embankments and courtyard spaces, taking into account the principles of biopositivity, are given. Experimental design models are proposed that consider the idea of transforming the existing public spaces of Crimean cities, taking into account modern international standards and information of sociological surveys